Kinetics study of Esterification Reaction of 2-Methyl-4-Chlorophenoxyacetic acid (MCPA Acid) - Kong, P.S.; Aroua, M.K.; Abdul Raman, Abdul Aziz (2011)
MCPA ester is a postemergence and selective herbicide widely used in controlling weed growth. This is due to the low solubility of MCPA ester in water which differs from majority of the other herbicides. With low solubility, the chance of water pollution is lesser comparatively. MCPA ester can degrade in soil by biological and biotic mechanism which reduces the soil pollution. Despite the wide application of this ester, the kinetic data on synthesis of MCPA ester is still considered as a proprietary data and it is not available in the open literature. Therefore kinetic studies are conducted in this work. MCPA ester was synthesized by reacting MCPA acid and 2-ethylhexanol in the presence of sulfuric acid as a catalyst. The parameters studied were reaction temperature, catalyst concentration and alcohol to acid molar ratio. The reaction was conducted in a jacketed batch reactor and samples were taken at an appropriate time intervals. The concentration MCPA ester was determined by gas chromatography mass spectrometry (GC-MSD) analysis. The experimental data were fitted with proposed homogeneous integrated second order kinetic model and the fitting accuracy at 373K, 383K and 393K were 0.99, 0.95 and 0.99 respectively. The activation energy and frequency factor were estimated to be 71.559 kJmol(-1) and 1.221 x 107 Lmol(-1) min(-1) respectively. Kinetic constant values were 0.844 x 103 to 6.331 x 103 Lmol(-1) min(-1) within the range of the temperature and concentration studied. As predicted, the activation energy decreases with increases in catalyst concentration and the values at 0.01M, 0.1M and 0.5M catalyst concentration were 73.6, 71.7 and 69.4 kJmol(-1) respectively.